Evidence from Indonesia on the legal policy confronting discrimination of minority groups based on race and ethnicity - Tara Nadya Andiani; FX Hastowo Broto Laksito; Jose Gama Santos (Faculty of Law, Universitas Slamet Riyadi, 2023)
The diversity of a multicultural society that supports Indonesia's national welfare has the opportunity to cause conflict and division, but there are still many acts of discrimination, especially against minority groups (race and ethnicity). Indonesia guarantees protection against discrimination as a constitutional right based on Article 281 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, Law No. 40 of 2008, Law No. 39 of 1999, even in the TAP MPR RI No. XVII/MPR/1998 on Human Rights. This research uses a normative method with a statute approach and is descriptive and qualitative. This discrimination violates human rights and is not in line with the principles of democracy and equality before the law. The Indonesian government has made various efforts to guarantee the rights of minority groups. Preventive efforts outside the law are still needed. Human rights, which were originally intended to secure the dimensions of human power as dignified beings, have been transformed into human rights that are considered to be full of dimensions of anthropocentrism, humanism, egoism, and false individualism. In terms of legislation, it is harmonious, but the practical implementation is still minimal, this can be seen from the lack of socialization of existing regulations related to racial and ethnic discrimination which still often occurs in the form of insults for certain races and ethnicities.